Optimal timing of operation for bleeding peptic ulcer: prospective randomised trial. - Morris, D L (1984)
From October 1980 to September 1983 all patients with upper gastrointestinal bleeding were admitted to a centralised unit and investigated by early endoscopy. A total of 142 patients with a proved duodenal or gastric ulcer were randomised after stratification for age and site of ulcer to early (aggressive) surgical management or a delayed (conservative) policy. Significantly more operations (n = 42; 60%) were performed in the early than in the delayed (n = 9; 20%) groups (p less than 0.01). There were no deaths among the 42 patients under 60. The overall mortality in the 100 patients aged over 60 was 10% and when analysed on an "intention to treat" basis there was no difference between early and delayed surgery. When, however, an unrelated death from a bleeding colonic polyp was excluded and the data analysed on "treatment received" the mortality was only 2% in the early group compared with 13% in the delayed group (p less than 0.05). When analysis was confined to gastric ulcer the difference between early (0%) and delayed (24%) treatment was even greater. The results of this trial indicate that for patients over 60 an aggressive surgical policy is associated with a significant reduction in mortality.